Canine Leproid Granuloma (CLG) - Clinical Signs, Diagnosis and Treatment: Granuloma leproide canino em Goiás Brasil - Moreira Lopes, Mariana; Rodrigues Ribeiro, Rafaela; Rodrigues de Souza Silva, Cinthya; de Campos Trentin, Thays; Martins Oliveira, Iago (Acta Scientiae Veterinariae, 2024)
Background: Canine leproid granuloma is a dermatopathy caused by the genus Mycobacterium spp. Limited information is available on this disease, which has predisposing factors such as breed and age. Its clinical manifestation consists of cutaneous or subcutaneous nodules of solid consistency, with a focal or multifocal distribution pattern, ulcerated and well-defined appearance, without pain upon palpation, and located around the head and ears, exhibiting characteristics of granulomatous inflammation. This case report aims to discuss the main aspects of the disease, its clinical symptoms, diagnostic methods, and instituted treatment. Case: A 5-year-old male dog, neutered, weighing 9.5 kg, was treated at a veterinary medicine school clinic. At the consultation, the main complaint was ulcerated lesions, and the time of onset could not be estimated by the owner. During the physical examination, dermatological lesions were found, mainly affecting the right periauricular region. The lesions were nodular, alopecic, exudative, and ulcerated. There were no changes in vital parameters, including heart and respiratory rates, mucosal evaluation, capillary filling time, systolic blood pressure, and rectal temperature. Laboratory analysis was performed, including hematology (complete blood count) and serum biochemistry (urea, creatinine, alanine aminotransferase, alkaline phosphatase, total proteins, and fractions). No alterations were found in the hematological evaluation that was performed. For diagnosis, cytopathological analysis was performed using fine needle aspiration cytology, which suggested the presence of bacilli of Mycobacterium spp. This conclusion arose due to the fact that under microscopy, activated macrophages containing intracytoplasmic structures with rod-like morphology were observed. To complement and confirm the diagnosis, culture and antibiogram were performed using the Ogawa Kudoh and Kirby Bauer methods, respectively, on samples from the lesions, which revealed the presence of concomitant bacterial infection caused by Aeromonas hydrophila. Based on this, broad-spectrum antibiotic therapy was started, based on enrofloxacin and rifamycin, for topical use. After the treatment, a reduction in the lesions was observed, along with clinical improvement. Discussion: Canine leproid granuloma is a poorly diagnosed disease, and so far, there are no studies that report the occurrence of the disease in most municipalities in the State of Goiás. Although it is asymptomatic, it is important to investigate the animal’s clinical condition through laboratory tests. Due to their characteristics, the dermatological lesions found in individuals with leproid granuloma suggest granulomatous inflammation, which requires further investigation to rule out other conditions with similar aspects and determine the definitive diagnosis. Therefore, knowing the diagnostic techniques that can be used, such as cytology, even though it is a screening test, was effective in this case because it demonstrated the cellular pattern of lesions, one of the predominant characteristics of the disease. The findings from the isolation of the agent highlight the importance of bacterial culture in this disease. Also, the use of antibiotics ensured wide coverage, demonstrating efficacy in the control of mycobacteriosis and secondary bacterial infection, contributing to the clinical improvement of the patient in this case. Keywords: canine mycobacteriosis, granulomatous inflammation, Mycobacterium spp. Título: Granuloma leproide canino (GLC) - sinais clínicos, diagnóstico e tratamento Descritores: micobacteriose canina, inflamação granulomatosa, Mycobacterium spp.